Encantados da “fortaleza” insular: D. Sebastião, natureza em uma história cultural na Amazônia - SILVA, Gerson Santos e (Universidade Federal do Pará, 2013)
When we apeak about popular culture, come to our thought of the commom sense, music, folklore and dance. We rarelly think in literature, but remember the religiosity that envolve all of these firsts. On that conception we don‟t remember to put the history, or better, the history that was produced for the people that made all of these manifestation and ideas. Here we try to think historically the genesis of a religiousness made in the middle of the Amazon region, with perspective of a sight of the people, the one who refers to when we speak about popular culture. From a site of the countryside of this region, São João de Pirabas city, we tried to see how this religiousness, represents in the nature and from it, to link a wider history with a Portuguese king character, D. Sebastian, religions with shamanism caboclo and afro-brasilian. Beyond the efforts of intelectuals and, also, show these religions from the thoughts of the people who made it, become it the most of the time, and answer, an alternative and at the same time part of the christian religion stabilished to our ancestrals that relaborated, as one the build of their history.